Port-site incisional hernia – A case series of 54 patients. (February 2017) - Lambertz, A.; Stüben, B.O.; Bock, B.; Eickhoff, R.; Kroh, A.; Klink, C.D.; Neumann, U.P.; Krones, C.J.
Abstract: Background: The increased use of laparoscopy has resulted in certain complications specifically associated with the laparoscopic approach, such as port-site incisional hernia (PIH). Until today, it is not finally clarified if port-site closure should be performed by fascia suture or not. Furthermore, the optimal treatment strategy in PIH (suture vs. mesh) is still widely unclear. The aim of this study was to present our experience with PIH in two independent departments and to derive possible treatment strategies from these results. Methods: Between 2003 and 2013, 54 patients were operated due to port-site incisional hernia in two surgical centres. Their data were collected and retrospectively analyzed depending on surgical technique of port-site hernia repair (Mesh repair group, n = 13 vs. Suture only group, n = 41). Results: Port site incisional hernia occurred in 96% (52 patients) after the use of trocars with 10 mm or larger diameter. Patients treated with mesh repair had significantly higher body mass index (BMI) (32 ± 9 vs. 27 ± 4; p = 0.023) and significantly higher rates of cardiac diseases (77% vs. 39%; p = 0.026) than patients in the suture only group. Mean fascial defect size was significantly larger in the Mesh repair group than in the Suture only group (31 ± 24 mm vs. 24 ± 32 mm; p = 0.007) and mean time of operation was significantly longer in patients operated with mesh repair (83 ± 47 min vs. 40 ± 28 min; p < 0.001). There were no significant differences in mean hospital stay (3 ± 4 days; p = 0.057) and hernia recurrence rates (9%; p = 0.653) between study groups. Mean time of follow up was 32 ± 35 months. Conclusions: In Port sites of 10 mm and larger diameter fascia should be closed by suture, whereas the risk of hernia development in 5 mm trocar placements seems to be a rare complication. Port-site incisional hernia should be treated by suture or mesh repair depending on fascial defect size and the patients' risk factors regarding preexisting deseases and body mass index. Highlights: This study is one of the largest series concerning port-site incisional hernia (PIH) regarding the current literature. In Port sites of 10 mm and larger diameter fascia should be closed by suture the current literature. PIH should be treated by suture or mesh repair depending on fascial defect size and the patients' risk factors.